Catalytic Enantioselective Synthesis of Glutamic Acid Derivatives via Tandem Conjugate Addition−Elimination of Activated Allylic Acetates under Chiral PTC Conditions - Ramachandran, P. Veeraraghavan; Madhi, Sateesh; Bland-Berry, Layla; Ram Reddy, M. Venkat; O'Donnell, Martin J (Journal of the American Chemical Society, 2005)
A new, general, and practical procedure for the asymmetric synthesis of 4-alkylidenyl glutamic acid derivatives via a catalytic enantioselective tandem conjugate addition−elimination on allylic acetates under chiral phase-transfer conditions is reported. A variety of structural types of allylic acetates have been reacted with the benzophenone imine of glycine tert-butyl ester to give the products in good to excellent yields and enantioselectivities (63−92% yield, 80−97% ee, 8 cases).